Cyclical thrombocytosis, acquired von Willebrand syndrome and aggressive non-melanoma skin cancers are common in patients with Philadelphia-negative myeloproliferative neoplasms treated with hydroxyurea. Issue 5 (May 2014) - Verner, Emma; Forsyth, Cecily; Grigg, Andrew
Abstract Cyclical thrombocytosis, acquired von Willebrand syndrome, aggressive non-melanoma skin cancers and other hydroxyurea complications have been reported in Philadelphia-negative myeloproliferative neoplasms (MPNs), but their incidence and clinical consequences have not been defined in a large cohort of patients. We conducted a retrospective analysis of 188 consecutive patients with MPNs specifically addressing the incidence of these complications. Cyclical thrombocytosis was documented in 29 patients (15%), the majority of whom were receiving hydroxyurea. Acquired von Willebrand syndrome was identified in 17 of the 84 screened patients (20%), but was not associated with any major bleeding complications. Non-melanoma skin cancers were reported in 51 patients (27%). Hydroxyurea-related fever occurred in nine of 149 patients (6%) who received hydroxyurea. Seventy-three patients (39%) experienced a total of 98 major thrombotic events, with the majority of these occurring prior to or within 3 months of the diagnosis. Cyclical thrombocytosis, acquired von Willebrand syndrome, aggressive non-melanoma skin cancers and other hydroxyurea-related complications are not infrequent in MPNs and have important clinical consequences for management.